Are Histological Examinations of Arthroplasty Specimens Performed Consistently Across the Country? A Large Database Study. Issue 8 (August 2019) - Suchman, Kelly I.; Poeran, Jashvant; Huang, Hsin-Hui; Mazumdar, Madhu; Bronson, Michael; Galatz, Leesa M.; Moucha, Calin S.
Abstract: Background: It is currently unknown to what extent routine histological examination of joint arthroplasty specimens occurs across hospitals nationwide. Although this practice is neither supported nor refuted by the available evidence, given the increasing demand for joint arthroplasties, it is crucial to study overall utilization as well as its main drivers. Questions/purposes: Using national data on joint replacements, we aimed to evaluate: (1) What is the current use of routine histological examination of joint arthroplasty specimens? (2) Does the use vary by geographic location and hospital characteristics? (3) Has use changed over time? Methods: From the Premier Healthcare database (2006-2016) we included claims data from 87, 667 shoulder (595 hospitals, median age 70 years, 16% nonwhite), 564, 577 hip (629 hospitals, median age 65 years, 21% nonwhite), and 1, 131, 323 (630 hospitals, median age 66 years, 24% nonwhite) knee arthroplasties (all elective). Our study group has extensive experience with this data set, which contains information on 20% to 25% of all US hospitalizations. Included hospitals are mainly concentrated in the South (approximately 40%) with equal distributions among the Northeast, West, and Midwest (approximately 20% each). Moreover, the Premier data set has detailed billing information, which allows for evaluations of real-world clinical practice. There was no missing information on the main variables of interest for this specific study. We assessed frequency of histology examination (defined by Current Procedural Terminology codes) overall as well as by hospital characteristics (urban/rural, bed size, teaching status, arthroplasty volume), geographic region (Northeast, South, Midwest, West), and year. Given the large sample size, instead of p values, standardized differences were applied in assessing group differences where a standardized difference of > 0.1 (or 10%) was assumed to represent a meaningful difference between groups. For significance of trends, p values were applied. Percentages provided represent proportions of individual procedures. Results: In most hospitals, histology testing was either rare (1%-10%, used in 187 of 595, 189 of 629, and 254 of 630 hospitals) or ubiquitous (91%-100%, used in 121 of 595, 220 of 629, and 195 of 630 hospitals) for shoulder, hip, and knee arthroplasties, respectively. Overall, histology testing occurred more often in smaller hospitals (37%-53% compared with 26%-45% in larger hospitals) and those located in the Northeast (59%-68% compared with 22%-44% in other regions) and urban areas (32%-49% compared with 20%-31% in rural areas), all with standardized differences > 10%. Histologic examination is slowly decreasing over time: from 2006 to 2016, it decreased from 34% to 30% for shoulder arthroplasty, from 50% to 45% for THAs, and from 43% to 38% for TKAs (all p < 0.001). Conclusions: Although overall use is decreasing, a substantial number of hospitals still routinely perform histology testing of arthroplasty specimens. Moreover, variation between regions and hospital types suggests that this practice is driven by a variety of factors. This is the first study addressing national utilization, which will be helpful for individual hospitals to assess how they compare with national utilization patterns. Moreover, the findings have clear implications for followup studies, which may be necessary given the exponentially growing demand for arthroplasties. Level of Evidence: Level III, therapeutic study.